INCLUSIVE MATHEMATICS EDUCATION IN JUNIOR HIGH SCHOOL THROUGH MERDEKA CURRICULUM - Muhammad Ari Subhi; Darhim (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
Every student possesses distinct learning needs that necessitate diligent efforts for fulfillment, particularly those requiring inclusive education. One of the pivotal strategies for meeting these requirements is through the curriculum. Presently, Indonesia employs the Merdeka Curriculum. This study aims to assess the efficacy of the Merdeka Curriculum in adequately facilitating inclusive mathematics education. The research methodology adopted involves document analysis. The principal focus of this research entails scrutinizing 12 regulatory documents and governmental policies concerning the Merdeka Curriculum and inclusive education, accessed through the Database Peraturan | JDIH BPK. The findings of this research are as follows: 1) The regulations and policies of the Merdeka Curriculum adequately accommodate students' learning needs through inclusive education, 2) Inclusive mathematics education is facilitated by the freedom to determine the flow of learning objectives and differentiation strategies, and 3) There are currently no guidelines or specific learning outcomes established in the field of mathematics for students with disabilities or exceptional intellectual and/or gifted abilities.